PROGNOSTIC SIGNIFICANCE OF INDEXED STROKE VOLUME IN ASYMPTOMATIC PATIENTS WITH MODERATE TO SEVERE AORTIC STENOSIS AND PRESERVED LEFT VENTRICULAR EJECTION FRACTION - Aleksandric, Srdjan; Miljkovic, Nina; Tomovic, Sara; Stefan; Djokovic, Aleksandra; Boskovic, Nikola; Dedic, Srdjan; Ostojic, Marina; Ristic, Marija; Ivan; Zivic, Katarina; sarenac, David; et al. (Medical Research, 2025)
Introduction and aim: Whether and when to intervene in asymptomatic patients with moderate to severe aortic stenosis (AS) and preserved left ventricular ejection fraction (LVEF) has not yet been determined. In patients with AS, low flow through the aortic valve is defined as indexed stroke volume (SVi) ≤35ml/m2. The aim of our work was to determine the relationship between SVi and all-cause mortality, as well as the prognostic significance of low SVi in asymptomatic patients with moderate to severe AS, high mean gradient across (Pmean) the aortic valve and preserved LVEF. Methods: The study included 121 asymptomatic patients (69 men, mean age 66±11 years) with moderate-to-severe AS (aortic valve area ≤1.5cm2), high Pmean across the aortic valve and preserved LVEF. The median follow-up was 38 months (IQR 35-42 months). Results: Ten patients (8%) died during the follow-up. All-cause mortality was significantly higher in the group of AS-patients with SVi ≤35ml/m2 compared with those with SVi >35ml/m2 (15% vs. 4%, p<0.045). The cumulative incidence of all-cause mortality was significantly higher in the group of AS-patients with SVi ≤35ml/m2 compared with those with SVi >35ml/m2 (log-rank p-value 0.035). After adjustment for outcome predictors, SVi was found to be the most significant predictor of all-cause mortality in the mid-term follow-up (adjusted-HR: 0.870; 95%CI: 0.801–0.945; p=0.001). Conclusion: The left ventricular SVi is an important predictor of all-cause mortality in asymptomatic patients with moderate-to-severe AS, high Pmean across the aortic valve, and preserved LVEF.